2021
DOI: 10.3390/antiox10091335
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Promotes Corticosteroid Insensitivity in Asthma and COPD

Abstract: Corticosteroid insensitivity is a key characteristic of patients with severe asthma and COPD. These individuals experience greater pulmonary oxidative stress and inflammation, which contribute to diminished lung function and frequent exacerbations despite the often and prolonged use of systemic, high dose corticosteroids. Reactive oxygen and nitrogen species (RONS) promote corticosteroid insensitivity by disrupting glucocorticoid receptor (GR) signaling, leading to the sustained activation of pro-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 305 publications
(367 reference statements)
0
18
1
Order By: Relevance
“…Corticosteroid insensitivity has been attributed to alterations in glucocorticoid receptor (GR) expression and diminished GR activity, enabling airway inflammation to persist in severe asthma ( Barnes, 2013 ; Lewis et al, 2021a ). To assess GR activity and its relationship to corticosteroid sensitivity, we measured expression of anti-inflammatory and antioxidant genes known to be regulated GR.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid insensitivity has been attributed to alterations in glucocorticoid receptor (GR) expression and diminished GR activity, enabling airway inflammation to persist in severe asthma ( Barnes, 2013 ; Lewis et al, 2021a ). To assess GR activity and its relationship to corticosteroid sensitivity, we measured expression of anti-inflammatory and antioxidant genes known to be regulated GR.…”
Section: Discussionmentioning
confidence: 99%
“…Prior works involving animal models and clinical studies have emphasized the role of eosinophils and neutrophils as effector cells in the pathogenesis of severe asthma [ 25 , 32 , 33 ]. Our findings align with many others where a close correlation between the location and activation of these cells with pathological changes such as airway hyperreactivity, mucus secretion, and peribronchiolar fibrosis were observed [ 25 , 32 , 33 ]. Steroid anti-inflammatory drugs are often effective inhibitors of airway eosinophilia, but higher doses are needed to block this event under severe asthma [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both inflammation and oxidative stress are critical players in the pathophysiology of steroid-insensitive asthma [ 33 , 43 ]. In line with this concept, we found that intranasal allergen stimulation led to a marked rise in oxidative damage, measured by MDA formation in the lung tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic obstructive pulmonary disease (COPD), a progressive airway disorder, is a major cause of disability and death worldwide, and the number of patients is increasing [ 1 ]. Smoking and air pollution leading to increased inflammation and free radicals in the respiratory tract cause an increased burden of oxidative stress, which leads to the development and progression of COPD [ 2 , 3 ]. Oxidative stress is reported to induce structural changes in the essential components of the lung, including irreversible damage to both the parenchyma and airway wall [ 4 ].…”
Section: Introductionmentioning
confidence: 99%